Prarancangan Pabrik Natrium Silikat Dari Natrium Oksida Dan Pasir Silika Kapasitas 75.000 ton Per Tahun - Setiawan, Yudha Satria; , Kusmiyati, S.T., M.T., Ph.D; , Ir. Herry Purnama, M.T., Ph.D (2017)
Sodium silicate factory with raw materials of sodium oxide and silica sand, the production capacity of 75,000 tons per year is planned to operate for 300 days per year. This factory will be established in the industrial park fire Tanjung Api, South Sumatra, with a land area of 45 160 m2 or 4.516 hectares and the number of employees 163 people. The process of making sodium silicate was performed using flow stirred tank reactor (RATB) by way merekasikan sodium oxide and silica sand. In the reactor the reaction at liquid-liquid phase, endothermic, with operating temperatures of 114 oC and a pressure of 1 atm. Sodium oxide feedstock requirements of 6326.5306 kg per hour, while the need for raw materials silica sand of 6247.3969 kg per hour. Sodium silicate products amounted to 9895.8333 kg per hour. Support utilities includes supplying process water extracted from the river of 120,844.55 kg per hour, the supply of saturated water vapor at 23832.050 kg per hour resulting from the process of heating water in the boiler, with diesel fuel amounted to 2017.013 liters per hour, Compressed air requirement of 100 psi or 6.8027 atm, and the provision of electricity obtained from PLN and generator sets of 649 kW in reserve the use of 295.678 liters of fuel per hour. Sodium silicate factory requires production costs of Rp.789.672.094.281. From the economic analysis of this plant showed a profit before tax of Rp 240,077,905,719.00 per year, 25% after tax profit reached Rp 180,058,429,289.00 per year. Percent return on investment (ROI) before tax 66.7% and 50.0% after taxes. Pay out time (POT) before taxes for 1.30 years and 1.67 years after tax. Break even point (BEP) of 50.01% and Shut down point (SDP) amounted to 38.76%. Discounted cash flow (DCF) accounted for 36.74%. From the data above feasibility analysis concluded that the plant is profitable and feasible to set.